1990
DOI: 10.1071/ch9901215
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Supercomputers in Modeling Chemical Reaction Kinetics: Kinetic Simulation of 'Quasi-Living' Radical Polymerization

Abstract: A computer program has been written which employs an implicit Euler method to solve directly the complete set of coupled differential equations which result from an analysis of polymerization kinetics. The program was written to make full use of the speed and power of modern supercomputers, and is suited to the solution of very large stiff systems of differential equations. The benefit of treating each propagation step as a discrete reaction is that information on the evolution of the molecular weight distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 1 publication
1
102
0
1
Order By: Relevance
“…[45] We did publish a theoretical paper that showed that NMP could, in principle, provide narrow polydispersity polymers. [46] The patent used the terms 'living', 'controlled-growth free radical polymerization', and 'step growth' and was a milestone in the renaissance of radical polymerization; the equivalent of the four minute mile.…”
Section: Termination In Copolymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] We did publish a theoretical paper that showed that NMP could, in principle, provide narrow polydispersity polymers. [46] The patent used the terms 'living', 'controlled-growth free radical polymerization', and 'step growth' and was a milestone in the renaissance of radical polymerization; the equivalent of the four minute mile.…”
Section: Termination In Copolymerizationsmentioning
confidence: 99%
“…A few years later we realised that in principle NMP was capable of yielding narrow MWD and we published a theoretical paper on what is now known as the persistent radical effect. [46] Polymer Structure Homopolymers, block copolymers (di-and tri-), as well as graft copolymers were described. Later we were to use NMP to produce microgels.…”
Section: Molecular Weight and Molecular Weight Distributionmentioning
confidence: 99%
“…The kinetic scheme for an ideal NMP reaction is the following (Scheme 1): reversible cleavage of alkoxyamines (so called -dormant‖ chain initiators) R 2 NO-R n into a propagating radical R n • and a persistent nitroxyl radical NO•, propagation, and irreversible termination. The theoretical background for this -ideal‖ mechanism and the optimal kinetic properties for the initiating alkoxyamine were presented previously by Fischer et al [5,6], Fukuda et al [7] and Solomon et al [8] and showed that side reactions, in particular H-atom transfer, have a detrimental effect on the controlled regime of polymerization. Even a minor side reaction on alkoxyamine homolysis leads to incomplete monomer conversion and an increase in the final polydispersity of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Advantageous to conventional free radical polymerization, LFRP can be applied to synthesize polymers 1 - 7 with narrow dispersity, block copolymers 8 -11 and dendrimers. 12 There are generally two ways to conduct LFRP, i.e., polymerization initiated by a pre-prepared unimolecular alkoxyamine, as well as that initiation by an initiator in situ in the presence of a SFR.…”
mentioning
confidence: 99%
“…12 There are generally two ways to conduct LFRP, i.e., polymerization initiated by a pre-prepared unimolecular alkoxyamine, as well as that initiation by an initiator in situ in the presence of a SFR. Most theoretical derivations 13 -18 and computer modeling 7 irreversible chain termination where I is initiator and R(O) is an initiator radical. SR(j) and R(j) are dormant chain and growing chain radicals, respectively, with chain length}; M is monomer; P(j) is "dead" polymers with chain length j and S represents stable radicals such as TEMPO.…”
mentioning
confidence: 99%